Efeitos da toxina botulínica tipo A associada à fisioterapia na morfologia muscular e mobilidade funcional em indivíduos pós-AVC : ensaio clínico randomizado - Freire, Bruno Bolla (2016)
Introduction: Stroke is the main cause of acquired adult disability and responsible for motor disorders, which the most common is spasticity. The spasticity increase involuntary muscle activity and promote adaptations in muscle morphology and functional performance. The aim of present study is to analyze the effects of botulinum toxin type a (BTA) for spasticity treatment associated with physiotherapy on muscle arquitecture and functional performance of plantiflexors in stroke survivors. Materials and methods: Randomized and controlled clinical trial with sample composed by 20 stroke survivors with ankle spasticity allocated in two groups: intervention group (BTA + physiotherapy) and placebo group (saline solution + physiotherapy). The muscle arquitecture of medial gastrocnemius was measured by fascicle length, penation angle and muscle thickness with ultrasonography, an isokinetic dynamometer was used to measure the force of plantiflexors and was used the fast gait 8 m, Time Up and Go (TUG) and Sit-to-Stand (STS) to mesure funcional performance. All subjects realized a physiotherapy program for 12 weeks. The intervention group used BTA on medial gastrocnemius and soleus muscle; placebo group used saline solution 0.9% on same muscles. Results: Intervention group showed ankle spasticity decrease after 4 and 12 weeks. Two groups showed no significant difference on fascicle length, penation angle and muscle thickness. Similar results were observed in plantiflexors force. Intervention group and placebo group showed execution time decrease in fast gait 8 m test, TUG and STS test after 12 weeks compared to pre-intervention; however, there was observed no difference between groups. Conclusion: Ankle spasticity decrease caused by BTA does not changed arquitecture muscle parameters or better performance in gait and basic functional mobility. Physiotherapy was enough to promote gain in fast gait and basic functional mobility.